PENENTUAN WAKTU PREVENTIVE MAINTENANCE TURBIN DENGAN METODE CRITICALITY ANALYSIS PADA PLTA SIPANSIHAPORAS - din aswan ritonga (Jurnal Simetri Rekayasa, 2019)
Population and economic growth makes electricity energy needs in Indonesia continue to increase every year. Based on the assumption of an average national economic growth growing at 6.1 percent per year and national population growth growing at 1.3 percent per year, according to the national electricity general plan for 2012-2031 Indonesia's average electricity demand is estimated at 11% per year. Increased electricity demand PT PLN (Persero) to be able to meet the needs of the community for electrical energy. Problems that arise in the company are specifically related to damage to the components in the Sipansihaporas hydropower unit which are composed of the main parts, namely turbines and generators. Damage to that section can result in downtime and delay in the production process which results in less effective and efficient machine performance. Effectiveness in the production process needs the right strategy to maintain the machine to operate is by determining the optimal maintenance time interval (Maintenance) of the equipment by using the criticality analysis method. After calculating the criticality analysis method, it was found that the guide vane and runner components are critical components. Furthermore, preventive replacement measures for the guide vane component can be carried out after operating for 4200 hours. The Runner component can also be performed after operating for 15800 hours or during overhaul. While the inspection action for the Guide vane component is performed after operating for 250 hours, the Runner component is carried out after operating for 1200 hours. After checking and checking the Avaibility value of the two components is above 95%